Polygamy and Identity: Deconstructing the woman Character in Selected Contemporary African Fiction - Amolo, Nelly Agunda (JOOUST, 2017)
Polygamy constitutes one of the distinctive features of African marriage. Recent studies indicate that polygamy is still widely practised and that one third of wives in monogamous relationships in sub-Saharan Africa are keenly aware of potentially becoming wives in polygamy. Today, polygamy remains one of the key thematic concerns of African creative writing. Previous literary studies have looked at the portrayal of women in African fiction and polygamy is cast largely as a site of male dominance and female victimhood. However, this study examines the possibility that contrary to traditional beliefs, women also play a primary role in the institution of polygamy. The purpose of this study is to analyse how women characters in the selected contemporary African fiction, are actively involved in manipulating polygamous marriages to their advantage and examine whether they do so in support of or against the institution of polygamy. Specifically, the study interrogates three African texts: Karooro Okurut's The Official Wife, Sue Nyathi's The Polygamist.eaui Lola Shoneyin's The Secret Lives of Baba Segi's Wives to examine how the 'women writers imaginatively and ideologically construct identities for their women characters in the family space through the representations of polygamy. The three texts, drawn from a population of African literary texts, both oral and written, thematising polygamy, were selected because they share thematic boundaries in both aesthetic and stylistic choices. The objectives of the study are to analyse the portrayal of women in polygamy in the selected contemporary African fiction, to examine how the choices made by women in the selected contemporary African fiction portray their identity as empowered agents in polygamy and to explore the extent to which female bonding among co-wives is exploited in the selected contemporary African fiction and how it portrays women's agency in polygamy. The study is qualitative in approach adopting the analytical research design. Qualitative data was generated through content analysis and. coded according to key thematic concerns, characterisation and the authors' commitments in the texts. The study adopted the womanist approach as its theoretical framework, particularly locating its discourse within the framework of Africana Womanism. This study ventures into the obscure role of women in initiating polygamy. The study demystifies the shady boundary line between victimhood and agency in polygamous marriages by exploring when women are considered 'victims' in need of protection and when as active 'agents' engaging with power and carving out their own spaces. The study found out that though contemporary African fiction writers still make women victimhood visible, they also make women agency possible. Women are steadily redefining and reshaping their polygamous world through valid choices and female bonding. The study recommends that contemporary writings should focus more on constructing positive identities for women to facilitate an African society that coheres in all aspects of life.
Keywords: Polygamy and Identity; Polygamy